Investigation and Trend Prediction of Disease Burden of Hypertensionin the Elderly Population Globally and in China from 1990 to 2021 - ZHAO Xiaoxiao; LU Xiaohui; KE Lixin; GAO Wulin; MENG Xiangran; REN Lili; DING Yunhan; ZHANG Qiang; XUN Yangqin; WU Jibiao; LU Cuncun (Xiehe Yixue Zazhi)
ObjectiveTo analyze the disease burden of hypertension in the elderly population from 1990 to 2021 and to predict future trends in China and globally, thereby providing insights for public health decision-making regarding older adults with hypertension in China.MethodsData on hypertension-related deaths and disability adjusted life years (DALYs) for individuals aged ≥60 years was extracted from the Global Burden of Disease (GBD)2021 database for the world, China, and five sociodemographic index (SDI) regions. Age-standardized mortality and DALYs rates for hypertension in the elderly population were calculated, and Joinpoint regression was used to assess trend changes of disease burden, with results reported as average annual percentage change (AAPC). Additionally, subgroup analyses were conducted based on age and sex. The relative impact of aging, population growth, and epidemiological changes on disease burden was analyzed using a three-factor decomposition method. Future projections for the disease burden from 2022 to 2040 were performed using a Bayesian model.ResultsFrom 1990 to 2021, both age-standardized mortality and DALYs rates for hypertension in the elderly population demonstrated a significant downward trend globally and in China (both AAPC values were negative, all P < 0.001). However, in 2021, the number of deaths attributed to hypertension among the elderly increased by 68.37% globally and by 157.85% in China compared to 1990, while DALYs rose by 61.74% globally and 125.98% in China. Notably, except for the high SDI region, the other four SDI regions witnessed significant increases in deaths and DALYs due to hypertension in 2021 compared to 1990. Furthermore, the burden of hypertension was generally higher among elderly males than females in China. In 2021, the highest number of DALYs due to hypertension was observed in the 70-74 years group, while deaths were predominantly concentrated in the 80-84 years group. Decomposition analysis indicated that population growth was the primary factor contributing to the increases in deaths and DALYs due to hypertension among the elderly globally and in China. Predictive analysis suggested that the disease burden of hypertension among the elderly in China, encompassing overall, male, and female populations, is expected to continue rising from 2022 to 2040.Conclusions Although age-standardized mortality and DALYs rates for hypertension among the elderly in China have shown a downward trend over the past three decades, the absolute burden remains substantial. There is an urgent need for the formulation and implementation of more effective public health policies and clinical interventions to address this critical public health challenge.